Status of fish culture in Rajshahi City Corporation of Bangladesh - Hossain, Md Rayhan; Flowra, Fawzia Adib; Islam, Saiful; Dey, Shishir Kumar; Sultana, Sayeeda (Asian Journal of Medical and Biological Research, 2017)
The present study carried on 16 sampling ponds in Rajshahi City Corporation, Rajshahi, Bangladesh during the period from August, 2005 to April, 2006. The main theme of this work was to find out the impact on present status of improved traditional culture and mixed culture in various pond. This study involved the observations made on physical characteristics, ownerships system, ponds preparation, stocking combinations of fish seeds, post stocking management and maintenance, harvesting and cost analysis of 16 improved traditional managed ponds in Rajshahi City Corporation. The primary data for the study was taken from the growers of these ponds. After collecting primary data, it was analyzed by suitable statistical method. Physical characteristics of the sampling pond were found. Water depth more or less sufficient, water colour greenish, presence of sunlight was sufficient, water source was mainly drain and rain and various shaped of pond was found. Pond was prepared by traditional method using pesticides (Phostoxin, Rotanone, Sumithion, Quick fume), lime and fertilizers (Urea, TSP., Cow dung). The fish seed were stocked in different ponds. In Sac fry was stocked in 4 nursery ponds. Post stocking management and maintenance were included inorganic fertilizer (Urea, TSP), organic fertilizer cow dung, applied weekly and supplementary feeds were used daily. It was observed that 15 ponds were made profit and one pond had loss. Two types of ownership were found (three years and five years) in the study period. During the study time two types of harvesting method were found. They were partial and final harvest. Mainly two types of production cost such as variable cost (lease, pond preparation, pesticide use, fertilizer etc.) and fixed cost (cost of net, net preservation, tax of pond etc.) were observed in the study period. Asian J. Med. Biol. Res. March 2017, 3(1): 94-102